2020
DOI: 10.1186/s13068-020-01843-4
|View full text |Cite
|
Sign up to set email alerts
|

LACCASE14 is required for the deposition of guaiacyl lignin and affects cell wall digestibility in poplar

Abstract: Background The recalcitrance of lignocellulosic biomass provided technical and economic challenges in the current biomass conversion processes. Lignin is considered as a crucial recalcitrance component in biomass utilization. An in-depth understanding of lignin biosynthesis can provide clues to overcoming the recalcitrance. Laccases are believed to play a role in the oxidation of lignin monomers, leading to the formation of higher-order lignin. In plants, functions of only a few laccases have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…The irregular xylem phenotype was observed in the stem of an Arabidopsis lac4 lac17 double mutant with 40% less lignin content [ 9 ]. The phylogenetically related laccase genes in different plant species, including Miscanthus sinensis [ 10 ], Brachypodium distachyon [ 11 ], and Populus tomentosa [ 12 ], were also found to be involved in lignification. More recent research identified two laccase genes from Japanese cypress ( Chamaecyparis obtusa ) with different oxidation activities towards H-type and G-type monolignols, contributing to the precise localization of H-type and G-type lignin in distinct cell-wall layers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The irregular xylem phenotype was observed in the stem of an Arabidopsis lac4 lac17 double mutant with 40% less lignin content [ 9 ]. The phylogenetically related laccase genes in different plant species, including Miscanthus sinensis [ 10 ], Brachypodium distachyon [ 11 ], and Populus tomentosa [ 12 ], were also found to be involved in lignification. More recent research identified two laccase genes from Japanese cypress ( Chamaecyparis obtusa ) with different oxidation activities towards H-type and G-type monolignols, contributing to the precise localization of H-type and G-type lignin in distinct cell-wall layers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…After transferring PtLAC22, PtLAC25, and PtLAC26 genes into lac2, the roots of the transgenic plants grew normally and responded to osmotic stress caused by PEG. The deposition of lignin usually occurs on the secondary cell walls of growing plants [65]. Excessive lignin deposition reduces the diameter of xylem ducts, restricting the transport of water and nutrients [66].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that in poplar, PtoLAC14 is mainly expressed in lignified tissues in the vascular bundles, such as the stem xylem, and that the overexpression of PtoLAC14 resulted in smaller cells with secondary wall thickening and an increased lignin content [ 56 ]. In Arabidopsis , AtLAC4 in interfascicular fibers and seed coat columella, AtLAC15 in seed coat cell walls, AtLAC14 in vascular tissues, such as roots, stems, leaves, petals and leaves but not in siliques (the fruit of Arabidopsis ), are uniquely expressed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%